DETERMINANTS AFFECTING THE INTENTION TO USE E-WALLET DURING COVID-19 IN MANADO - Jeason Lucky Alexander Tampi; Joy Elly Tulung; Fitty Valdi Arie (Universitas Sam Ratulangi, 2023)
Currently, the international economic sentiment has been influenced greatly with the Covid-19 pandemic and are still in the process of adjusting and conforming to the changes in societal and market lifestyle. E-wallet as Cashless payment methods have become a trend everywhere especially with the Covid-19 pandemic that caused people to limit physical contact with other people. This study aims to analyze the effect of Perceived Ease of Use, Perceived Risk and Social Influence as determinants towards the Intention to Use E-wallet during Covid-19 in Manado. This study employs casual research in quantitative approach. The population studied in this study is the people in Manado. Survey data were collected and collated from 100 respondents through google form, ranging from student to working employees and entrepreneurs. This study uses Multiple Regression Analysis to process the data. The findings confirm that Perceived Ease of Use, Perceived Risk, and Social Influence positively affects the Intention to Use E-wallet during Covid-19 in Manado. Based on the outcome of this study, it is recommended for E-wallet industry companies to increase public awareness of the use of e-wallet by informing it through public mass communication or social media and therefore, more people become aware and easier to have intention to use. Keyword: e-wallet, perceived ease of use, perceived risk, social influence, intention to use